Long-term prognosis of treated acute massive pulmonary embolism. Issue 10 (October 1977) - Hall, R J; Sutton, G C; Kerr, I H
Abstract : Seventy-two patients surviving initial treatment by pulmonary embolectomy, streptokinase, or heparin for acute massive pulmonary embolism have been reviewed 1 to 9 years later. Of these patients, 17 had additional cardiorespiratory disease. There were 12 late deaths (41% of those patients with, and 9% of those patients without additional cardiorespiratory disease). No death was due to chronic pulmonary hypertension, and none to certain recurrence of pulmonary embolism. The causes of death were malignant disease (6 patients), cardiopulmonary disease other than pulmonary embolism (4 patients), and 'sudden' (2 patients). Though venous interruption surgery was not used, and long-term anticoagulation rare, the incidence of possible or probable recurrent embolism was low (6%). There was no definite evidence of persistence or subsequent development of pulmonary hypertension after treatment in any patient. Resolution of embolism as judged by symptoms, signs, electrocardiogram, and chest x-ray examination was almost always complete. Some pulmonary arteriograms 1 to 6 months after initial treatment showed minor abnormalities, but others at a later date were normal. Perfusion lung scans carried out 1 to 8 years after initial treatment often showed minor abnormalities.